Perlindungan Hukum Terhadap Pengguna Aplikasi E-Wallet Dana - Hartanto, Hartanto; Rosadi, Vincent; Yosmar, Ervin Alvaro (Postgraduate Program Doctoral in Law, Universitas Pattimura, 2023)
Introduction: It is becoming easier for people to use the internet, which previously had to be done in an internet cafe, but now it is quite practical to use a smartphone/Android. This opportunity is attractive for funding application service providers to develop their business in various ways. The impact is that people's hedonism as consumers increases while the risk of problems increases. Purposes of the Research: To determine legal protection for consumers for users of the DANA E-Wallet application Methods of the Research: This research is normative legal research, to find legal norms related to consumer protection for the use of the DANA E-Wallet, while the data source used is secondary data. Results of the Research: There are still difficulties in obtaining accountability from DANA if losses occur to consumers. The government has taken preventive action by also issuing laws regulating electronic transactions. The security of personal data (privacy) of users must be protected from being the responsibility of the service provider, and if losses result from leaking of personal data, then the service provider can be asked for compensation.